PENDEKATAN FILOLOGIS DAN SHAR? AL-?AD?TH DALAM KRITIK HADIS ANCAMAN DAN GANJARAN MEMBACA AL-QUR'AN - Achmadana Syachrizal Rizal; Ahmad Hanafi (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
This research focuses on manuscripts owned by Khomsatun, containing various texts, including hadiths discussing threats and rewards in reciting the Qur'an. The primary objective of this study is to present a critical edition of the texts and elucidate the meanings of these hadiths through the approach of ?har? al-?ad?th. The research methodology employed is qualitative, utilizing philological and shar? al-?ad?th approaches. Data collection techniques are conducted through documentation. Three hadiths cited by the compiler were found not to originate from primary hadith sources. The first hadith cannot be further researched as it is proven not to be a hadith. The second hadith, despite differences in authenticity assessments, contains a profound understanding of the position of Surah al-Baqarah as the core of the Qur'an and the virtue of Ayat al-Kursi encompassing divine teachings. The third hadith, although considered ?a‘?f, still conveys an important message about the significance of prayer and reciting the Qur'an as means to draw closer to Allah.